The Strategies Used By English Language Learners To Learn Grammar - Hermansyah, Sam; Sadapotto, Andi; Hambing, Agus; Rambung, Herna (La Ogi : English Language Journal, 2021)
This study sought to identify the various types of learning techniques used by Muhammadiyah Sidenreng Rappang University students enrolled in the English education study program. Seventy-five first-semester students who were enrolled in a basic English grammar course served as the study's subjects. Data collection and analysis were conducted using descriptive quantitative. The study's findings indicated that metacognition (20, 93%), cognitive (18, 49%), social (17, 83%), affective (16, 48%), memory (15, 97%), and compensatory (10, 25%) were the learning strategies that students used the least when studying grammar. Additionally, the ability to focus on a specific grammar pattern, attempt to grasp it, and make connections to previously learned material is another reason why students frequently employ metacognitive strategies when studying grammar. As a result, it is recommended that teachers should be aware of the various learning strategies and then assist the students as they study in order to improve learning outcomes.